Risks and Impacts of Chromium Metals on Human and Ecosystem Health - Putra, Adewirli; Arman, Eliza; Fitri, Wiya Elsa; Mayaserli, Dyna Putri; Putra, Arief Yandra; Febria, Fuji Astuti (Al-Kimia, 2024)
This article discusses the harmful effects of chromium metal on human health and the environment. This review aims to provide an in-depth understanding of its negative implications. Analysis of relevant studies provides a comprehensive picture of how Cr (VI) exposure seriously impacts human health and threatens environmental safety. This review method was conducted by identifying and selecting relevant sources through the scientific journal databases PubMed, Google Scholar, and ScienceDirect with the keywords "Cr(VI)," "health risk," "environmental impact," and "chromium metal" then selected and evaluated by considering the quality of the journal, research methodology, and findings. In terms of human health, exposure to Cr(VI) has been shown to increase the risk of death from cardiovascular disease and has significant carcinogenic potential. The impact is not limited to this; Cr(VI) exposure can also cause respiratory problems and skin irritation in industrial workers. In terms of the environment, releasing Cr(VI) into the air, water, and soil threatens living ecosystems. The impact of Cr(VI) pollution on the water and soil environment is of great concern to the quality of water resources and plant growth. In addition, releasing Cr(VI) into the air around industrial plants can also endanger the health of local communities. Therefore, this article highlights the importance of stricter monitoring of chromium-using industries and promoting safer and environmentally friendly alternatives. Implementing preventive and protective measures is essential to minimize the negative impacts of chromium metal on human health and the environment. Using safer alternatives and environmentally friendly production technologies should also be encouraged to create a sustainable and healthy environment for all living beings.